Design and construction of a microcontroller-based heartbeat monitoring device with display - Onuiri, Ernest; Madu, Nissi; Adeagbo, Boluwatife; Johnson, Iniobong; Awodele, Oludele (International Journal of Engineering and Technology, 2014)
Strong indications have emerged the world over that a large proportion of people in developing countries are now at great risk of developing cardiovascular (heart) diseases which currently accounts for one-third of all deaths worldwide. The need for an accurate, yet affordable ECG (Electrocardiogram) machine is necessary to ensure the quality of cardiovascular health of the average citizen. This research entails the design and implementation a portable, easy-to-use ECG machine. The heartbeat rhythm was obtained using 12-lead ECG electrodes and displayed in a waveform using a GLCD (Graphic Liquid Crystal Display) screen. Interpretation of the heartbeat rhythm was done by the use of red and blue LEDs (Light Emitting Diodes) indicating normal and abnormal heartbeat rhythms which are stored on an SD card for easy retrieval, thereby ensuring a user-friendly design. The significance of this design lies in its potential to empower patients with heart conditions by providing a means of monitoring progress in the areas of drugs being administered, effects of surgical repairs and general well-being of the patient. Keywords: Heart Monitor, Electrocardiogram, Heartbeat, Heart Rate, Cardiovascular Diseases, Heart.